2020
DOI: 10.3390/su12093624
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Microorganisms Colonizing the Surface of Polystyrene Samples Exposed to Different Aqueous Environments

Abstract: The contamination of marine and freshwater ecosystems with the items from thermoplastics, including polystyrene (PS), necessitates the search for efficient microbial degraders of these polymers. In the present study, the composition of prokaryotes in biofilms formed on PS samples incubated in seawater and the industrial water of a petrochemical plant were investigated. Using a high-throughput sequencing of the V3–V4 region of the 16S rRNA gene, the predominance of Alphaproteobacteria (Blastomonas), Bacteroidet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Its significant reduction from 81.2%, 7 phylogenetic groups in MKC-C to 3.7%, only one species in MKC-P resulted in flourishing of Meiothermus and Brevibacillus in MKC-P that suggested an active participation of these genera in the degradation process. Similar domination of polymer-active taxa in plastic containing samples has been reported for some marine communities [29,30]. Unfortunately, a comparison among the composition of thermophilic communities with and without plastic is not possible due to the lack of such information.…”
Section: Discussionsupporting
confidence: 68%
“…Its significant reduction from 81.2%, 7 phylogenetic groups in MKC-C to 3.7%, only one species in MKC-P resulted in flourishing of Meiothermus and Brevibacillus in MKC-P that suggested an active participation of these genera in the degradation process. Similar domination of polymer-active taxa in plastic containing samples has been reported for some marine communities [29,30]. Unfortunately, a comparison among the composition of thermophilic communities with and without plastic is not possible due to the lack of such information.…”
Section: Discussionsupporting
confidence: 68%
“…The metabolism of carbohydrates, fatty acids, amino acids and even antibiotic resistance genes were more abundant in the rainy season (Supplementary Figures 4, 5), when the bacterial microbiota was richer (Figure 2). The inference of metabolism based on 16S sequencing has already been used to compare the gut microbial communities of human populations living in urban and tribal areas (Singh et al, 2019), landfill sites with different characteristics (Thakur et al, 2020), and polystyrene-degrading biofilms cultivated under different conditions (Tourova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the biological diversity in biofilms formed on PS samples incubated in Black Sea water at 10 °C and industrial water from a petrochemical plant revealed different community composition [ 70 ]. It was suggested that the significant difference in salinity may be reflected in the active growth of slight halophiles in sea water samples (1.86% salinity) and non-extremophiles in industrial water samples (~0.1% salinity).…”
Section: Halophilic Degradersmentioning
confidence: 99%